2017
DOI: 10.1177/1403494817720103
|View full text |Cite
|
Sign up to set email alerts
|

Good work ability among unemployed individuals: Association of sociodemographic, work-related and well-being factors

Abstract: The findings provide further evidence on the factors related to good work ability of the unemployed. These factors should be considered when designing interventions for promoting work ability and to minimise the harmful effects of long-term unemployment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Although the aspects of functioning were related to changes in work ability, the effects became weaker as perceived health and the length of unemployment were included in the model. The significance of health in assessing perceived work ability has been noted in earlier studies (Hult et al 2017;Ferreira et al 2015;McGonagle et al 2015;van de Vijfeijke et al 2013;Kuijer et al 2012;Ahlstrom et al 2010). Our results were concurrent with the results of these earlier studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although the aspects of functioning were related to changes in work ability, the effects became weaker as perceived health and the length of unemployment were included in the model. The significance of health in assessing perceived work ability has been noted in earlier studies (Hult et al 2017;Ferreira et al 2015;McGonagle et al 2015;van de Vijfeijke et al 2013;Kuijer et al 2012;Ahlstrom et al 2010). Our results were concurrent with the results of these earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…The proportions of unemployed persons who perceive themselves as having good work ability (a score of eight or above on a scale of 0-10) vary between 30% and 60% in different studies (e.g. Hult and Lappalainen 2018;Hult et al 2017;Kerätär et al 2016;Szlachta et al 2012). The associations of unemployment and health vary depending on the economic situation of the household, perceived health status, personal relationships, the sense of ability to work, social roles and the individual perception of one's life position (Brand 2015;Worach-Kardas and Kostrzewski 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unemployed have lower work ability than those who are employed [21][22][23][24]. Contemporary working life places new and rapidly increasing demands on individuals' work ability, functioning and employability [25].…”
Section: Introductionmentioning
confidence: 99%
“…In these services, work ability and functioning often need to be assessed individually, but this assessment is difficult in many ways in the case of those in a weak labour market position. It has been suggested that the resources of, for example, health services should focus more on those whose perceived health and work ability has started to decline [14,26]. It has also been recognised that many work ability limitations go unnoticed by services, leading to opportunities for rehabilitation being unused [27,2,28].…”
mentioning
confidence: 99%